The Utilization of an Improvised Fuming Device in the Development of Latent Fingerprint - Hazel Ann Asoy; Fernando Amaro; Eleonor Villaruz; March Jale Paradiang; Divina Torralba; Edzel Peña; Wendell Malarasta (Future Science / FSH-PH Publications, 2026)
Developing latent print is an important process in investigating a person’s identity for the solution of a case. There are different types of developing latent prints that are being used by the Fingerprint Examiner. Cyanoacrylate or superglue reacts with the moisture present on the latent print. It is one of the most effective methods of developing latent print. There are various types of fuming chambers that are used in this method that can be bought in the markets, but they cost a lot of money; many of the fuming chambers present in the market do not have specific sizes. Fingerprint analysis is a crucial part of forensic science, serving as an important tool in identifying a person link with the crimes. The traditional method of developing latent fingerprints using cyanoacrylate has limitations that require innovative solutions. The current study differs from this study, which only focuses on developing fingerprints on portable objects. To address the challenges related to the size of the fuming box, the participants recommended using different sizes - small, medium, and large - depending on the size of the evidence being processed. To address the challenge of fuming box size, it is advisable to equip forensic laboratories with a range of fuming box sizes, including small, medium, and large options. This will allow the Fingerprint Examiner to match the size of the evidence with an appropriate fuming box, ensuring efficient and effective development of latent prints.